Comparison of Tooth and Arch Dimensions in Dental Crowding, Spacing, and Normal Dentition: A Cross-Sectional Study from a Tertiary Orthodontic Centre in Nepal - Shrestha, Natasha; Bhattarai, Anisha; Shahi, Swati Singh; Sharma, Shakti (Journal of Bharatpur Hospital, 2026)
Background Dental crowding and spacing are the most common malocclusions worldwide, arising from imbalance between mesiodistal tooth size and dental arch dimensions (TSALD), yet Nepalese comparative morphometric data are limited. This study aimed to compare MD tooth dimensions, arch perimeter, IC, IP, IM widths, arch depth, and TSALD across crowded, normal, and spaced dentitions in maxillary and mandibular arches Methods This cross-sectional study analyzed 138 pretreatment orthodontic casts (age 19-34 years) from College of Medical Science-Teaching Hospital, Nepal. Based on TSALD, samples were categorized into crowded (≤ −4 mm; n=22), normal (0 ± 3 mm; n=22), and spaced (≥ +4 mm; n=94). MD widths of all permanent teeth (excluding second and third molars) were measured using a digital Vernier caliper. Arch perimeter was assessed using a brass-wire method. One-way ANOVA with Tukey post-hoc tests was applied (α=0.05). Results Total maxillary tooth material was highest in crowded cases (75.62 ± 5.46 mm) and lowest in spaced cases (69.52 ± 4.75 mm; p<0.001). Maxillary arch perimeter increased significantly from crowded (70.73 ± 5.35 mm) to normal (76.91 ± 3.28 mm) and spaced groups (78.90 ± 4.69 mm; p<0.001). A similar trend was observed in the mandible (62.09 ± 3.18 mm; 65.41 ± 3.35 mm; 67.73 ± 4.52 mm; p<0.001). TSALD values confirmed classification in both arches (maxilla: −4.89 to +9.38 mm; mandible: −2.30 to +6.88 mm; p<0.001). IC width showed no significant intergroup differences. Conclusions Both tooth size and arch dimensions contribute to TSALD, with arch perimeter showing a stronger discriminatory role. Independent assessment of maxillary and mandibular TSALD is essential for arch-specific orthodontic treatment planning in Nepalese patients.